Pengenalan Proses Sertifikasi Halal Pada Pelaku Usaha Mikro Dan Kecil - Arfah, Lita; Marro'aini, Marro'aini; Sakinah, Nur; Jonkenedi, Jonkenedi; Martha Darman, Dian (Al-Umm: Jurnal Pengabdian dan Pengembangan Masyarakat, 2024)
Halal certification is a process that is a necessity for meeting a wide market share, including benefits for entrepreneurs trading goods or services. On the consumer side, halal certification is proof of the seriousness of entrepreneurs in fulfilling the halal status of merchandise, whether in the form of goods or services. In the framework of the Tridharma of lecturers in the field of sharia finance in the Sharia Business Management study program, the author provides knowledge to Community Service regarding the halal certification process in the target area: Tuah Madani Village, Pekanbaru. This implementation is aimed at the household environment in the sub-district. The aim of this community service is to provide knowledge about the halal certification process and related understanding, which is fundamental according to the 2021 BPJPH regulations, including the type of business, size of the company, length of the process, and fees charged. After the presentation, the author carried out a direct evaluation of the participants by means of question and answer to test that the participants had understood the things presented as appropriate information to help the existence of sharia-compliant businesses